Factors associated with inadequate Hospitalizations of older adults in the Emergency Department of the Hospital Edgardo Rebagliati Martins 2017: Factores asociados a Hospitalizaciones inadecuadas de adultos mayores en el Servicio de Emergencia del Hospital Edgardo Rebagliati Martins 2017 - Capcha Serna, Lulio E. (2022)
Introduction:Inadequate hospitalizations (IH) alter hospital management and much more when they are carried out in the elderly population; therefore, identifying the factors is relevant at the national and local levels. Objective: To determine the factors associated with IH in older adults in the Emergency Service (ES) of the Edgardo Rebagliati Martins National Hospital (HNERM) during 2017. Methods: Observational, analytical, cross-sectional study. A sample of 414 patients randomly selected from 18 250 patients admitted during the study period was selected. Collection forms were used, and medical records were reviewed. With the help of the SPSS 25 program, the Chi-square test was performed, and the simple Prevalence Ratio (PR) and adjusted (Rpa) were calculated. The level of signicance was 5%. Results: The frequency of IH was 11,8%. The epidemiological factors associated with IH were ages from 75 to 84 years RPa=5,80 (2,20-15,27) and from 85 to more years RPa=8,22 (2,76-24,44), the female sex RPa=2,20 (1,11-3,10), the occupation as a housewife RPa=3,39 (1,13-10,17) and the accompaniment of the spouse RPa= 9,16 (2,59-32,38), child RPa= 3,72 (1,14-12,14), parents RPa= 8,50 (1,88-38,44) and siblings RPa=22,42 (5,78-86,97). The organizational factors associated with IH were internist treating physician RPa=2,90 (1,38-6,07) and admisiion morning shift RPa=4,84 (1,67-14,06). Conclusions: There are factors associated with IH in older adults in the SE of HNERM.